Cerita, Boneka Jari, dan Hadiah: Intervensi Terpadu dalam Mendukung Perkembangan Regulasi Emosi dan Kesehatan Mental Anak Usia Dini - Riza Fitriana (SEHATI: Jurnal Kesehatan, 2026)
This study aims to enhance emotion regulation in early childhood through an integrated intervention as an effort to strengthen children’s mental health. The subject of this study was KS, a 5 year 8 month old boy who showed low emotion regulation abilities, characterized by frequent tantrum behaviors such as crying loudly, screaming, and throwing objects when his needs were not met. These behaviors were influenced by a difficult temperament, permissive parenting style, and limited parental attention due to work demands. This study employed a Single Subject Research (SSR) design with observations conducted over a two-week intervention period. The integrated intervention included the introduction of basic emotions through storytelling using emotion stickers and finger puppets, implementation of a token economy technique to reduce tantrum behaviors, and psychoeducation for teachers and parents. The results demonstrated an improvement in KS’s emotion regulation abilities. KS was able to recognize and understand basic emotional expressions and showed better control of anger. Based on the Emotion Regulation Checklist (ERC), KS’s emotion regulation increased from a low category to a moderate category according to the teacher’s assessment and to a high category according to the parents’ assessment. In addition, the token economy technique effectively reduced the frequency of tantrum behaviors at school. These findings indicate that integrated intervention is effective in improving emotion regulation and strengthening mental health in early childhood